Further evidence of novel APOB mutations as a cause of familial hypercholesterolaemia. (October 2018) - Alves, Ana Catarina; Benito-Vicente, Asier; Medeiros, Ana Margarida; Reeves, Kaajal; Martin, Cesar; Bourbon, Mafalda
Abstract: Background amd aims: APOB mutations are a rare cause of familial hypercholesterolaemia (FH) and, until recently, routine genetic diagnosis only included the study of two small APOB fragments. In previous years, 5 novel functional mutations have been described in APOB fragments not routinely studied, our group having functionally characterized 2 of them. The main aim of this work was to identify and characterize novel alterations in APOB to assess the genetic cause of hypercholesterolemia in patients with a clinical diagnosis of FH. Methods: We performed next generation sequencing of 48 Portuguese clinical FH patients, who were apparently mutation negative. All variants found in APOB were annotated. For functional studies, LDL from index patients and relatives was separated and marked with FITC-LDL for flow cytometry assays in lymphocytes and U937 growth assays. Results: A total of 11 potential pathogenic variants were identified. Variants p.(Pro994Leu) and p.(Thr3826Met) in exons 19 and 26 were found in 4 patients, and in vitro analysis was performed for these variants. An exon 26 alteration (p.(Thr3826Met)) showed a decrease in binding and internalization of LDL, and in U937 growth assays that was similar to the effect with p.(Arg3527Gln). An alteration in exon 19 had a neutral effect. Conclusions: The spectrum of functional alterations in APOB outside the fragments routinely screened is slowly growing. Screening of all 29 exons of APOB is advised for FH routine diagnosis, but functional characterization is necessary for pathogenicity assessment. It is expected that the number of patients with functional APOB mutations will increase in the near future. Highlights: The spectrum of functional alterations in APOB outside the fragments routinely screened is growing. We characterized two rare novel variants in APOB, p.(Thr3826Met) is pathogenic and p.(Pro994Leu) is neutral. The study of all 29 exons of APOB should be performed in routine diagnosis, now possible by NGS, since it is expected that a further 5–10% of clinical FH patients can have FH due to a novel APOB mutation. Due to low penetrance of APOB variants and high rate of common variants in APOB, all novel variants need to be functionally characterized to prove their pathogenicity.